Adalékok az 1921. évi III. törvénycikk alapján indított büntetőperekhez - Lehotay, Veronika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
At the beginning of the period between the two world wars, new categories were introduced in criminal law (such as national hate speech and national defamation) based on the provisions of the Act III of 1921. These categories enabled to prosecute the enemies of the system or to silence the people who criticized the system in some way. Many of the 'accused' were peasants living in difficult conditions and poverty, as well as workers and industrialist. Besides them there were also writers who depicted inhumane living conditions in their works, thus they had to answer in court. The cases presented in this study serve as examples to illustrate these procedures.